Expedient Synthesis of Core Disaccharide Building Blocks from Natural Polysaccharides for Heparan Sulfate Oligosaccharide Assembly. (6th November 2019) - Pawar, Nitin J.; Wang, Lei; Higo, Takuya; Bhattacharya, Chandrabali; Kancharla, Pavan K.; Zhang, Fuming; Baryal, Kedar; Huo, Chang‐Xin; Liu, Jian; Linhardt, Robert J.; Huang, Xuefei; Hsieh‐Wilson, Linda C.
Abstract: The complex sulfation motifs of heparan sulfate glycosaminoglycans (HS GAGs) play critical roles in many important biological processes. However, an understanding of their specific functions has been hampered by an inability to synthesize large numbers of diverse, yet defined, HS structures. Herein, we describe a new approach to access the four core disaccharides required for HS/heparin oligosaccharide assembly from natural polysaccharides. The use of disaccharides rather than monosaccharides as minimal precursors greatly accelerates the synthesis of HS GAGs, providing key disaccharide and tetrasaccharide intermediates in about half the number of steps compared to traditional strategies. Rapid access to such versatile intermediates will enable the generation of comprehensive libraries of sulfated oligosaccharides for unlocking the "sulfation code" and understanding the roles of specific GAG structures in physiology and disease. Abstract : Die vier Disaccharide, die für die Herstellung von Heparansulfat (HS)/Heparin‐Oligosacchariden benötigt werden, wurden aus natürlich vorkommenden Polysacchariden synthetisiert. Der schnelle Zugang zu diesen wichtigen Bausteinen sollte die Erstellung umfassender HS‐Oligosaccharid‐Bibliotheken und somit Untersuchungen zur Rolle von Glycosaminoglycanen in physiologischen Prozessen erheblich erleichtern.